TRIBOLOGICAL TESTING AND STRUCTURAL ADAPTATION OF POLYMER COMPOSITES - Marchuk, Roman; Mnatsakanov, Rudolf (Problems of Friction and Wear, 2026)
Polymer composites are increasingly applied in sliding friction units due to their low friction coefficient, chemical resistance, and ability to adapt structurally under mechanical loading. One of the key parameters determining their performance is microhardness, which may change during operation and thus reflect the material’s capacity for structural adaptation. This study presents the results of tribological testing of several polymer composites, including industrial and laboratory-prepared materials, with a focus on microhardness variation and wear resistance under different sliding regimes. Three types of composites were investigated: - Zedex zx‑324V2T (PEEK + PTFE): a commercial composite combining high thermal stability and mechanical strength of PEEK with the low friction and antiwear properties of PTFE. - Polystyrene/graphite composite (PS‑6): prepared by suspension polymerization, where graphite acts as a solid lubricant and reinforcement. Literature reports indicate that graphite addition influences polymerization kinetics, particle size, and molecular weight, while also reducing thermal conductivity and improving foam uniformity. - Epoxy resin composites (Epikote LR285 + graphite): experimental samples fabricated with varying graphite concentrations (7.9%, 14.6%, 20.5%), cured under controlled thermal conditions to ensure homogeneous filler distribution. Tribological tests were performed under three sliding speeds (1.4, 2.8, and 5.5 m/s) using steel counter bodies. Microhardness was measured before and after testing with a PMT‑3 microhardness tester, while weight loss was recorded to evaluate wear. The results reveal distinct behaviors depending on composite type: - Epoxy-based composites exhibited a decrease in microhardness after testing, with higher graphite content mitigating but not eliminating softening effects. - The PS‑6 composite demonstrated an increase in microhardness (ΔH = 64 MPa), indicating structural adaptation through molecular orientation and surface densification, accompanied by relatively low wear. - Zedex zx‑324V2T showed the most pronounced strengthening effect, with microhardness increasing up to ΔH = 305 MPa at higher sliding speeds, while wear decreased due to the formation of a stable PTFE-based transfer film. These findings confirm that structural adaptation is a critical mechanism for enhancing the tribological performance of polymer composites. The degree of adaptation depends strongly on the polymer matrix and filler type. Practical significance: The results provide guidance for optimizing composite formulations intended for sliding bearings and friction units operating under severe conditions. In particular, PEEK/PTFE systems and polystyrene/graphite composites demonstrate promising self-strengthening behavior, opening pathways for the development of advanced self-adaptive polymer materials for automotive, aerospace, and energy applications